2018
DOI: 10.1080/01933922.2018.1484539
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Growth Factors in Experiential Training Groups Through Tuckman’s Conceptual Model

Abstract: Diseño de implementación del modelo Tuckman en la red de agencias de giros y finanzas 9 4.1 ¿Cómo los líderes de oficina escogen a los integrantes del equipo de alto rendimiento? .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…While Tuckman's (1965) model is over half a century old, it is considered valid and pertinent in examination of group dynamics. This was supported by Kiweewa et al (2018) in a recent study that examined growth factors in experiential training groups. They found the growth factors varied over time across different stages of group development, supporting Tuckman's (1965) original model.…”
Section: Conceptual Frameworksupporting
confidence: 53%
“…While Tuckman's (1965) model is over half a century old, it is considered valid and pertinent in examination of group dynamics. This was supported by Kiweewa et al (2018) in a recent study that examined growth factors in experiential training groups. They found the growth factors varied over time across different stages of group development, supporting Tuckman's (1965) original model.…”
Section: Conceptual Frameworksupporting
confidence: 53%
“…One way this strategy may be exemplified includes the researcher examining the multiplicity of roles and engaging radical reflexivity to explore the complexities that can result within the research process. For example, counseling and counselor education researchers often study experiences within counseling, teaching, and supervision (Gordon & Luke, 2016;Kiweewa et al, 2018;Luke & Goodrich, 2017), and in doing so, can encounter role conflicts. As part of such an investigation , I (the second author) was the instructor of record within a course wherein course-related data were being collected.…”
Section: Applicationmentioning
confidence: 99%
“…Scholars also conducted research on evaluating methods related to group counseling courses with a focus on growth groups. Researchers found that not sharing journals led to faster creation of group cohesion (Oh et al, 2018), identified growth factors that varied over group stages and time (Kiweewa, Gilbride, Luke, & Clingerman, 2018), and reported student experiences in a group course grounded in relational‐cultural theory (Hall, Harper, & Korcuska, 2018). Additionally, the literature on multicultural courses included evidence that photovoice deepened learning and helped students express emotions (Paone, Malott, Pulliam, & Gao, 2018); use of popular films to teach multicultural counseling (Nittoli & Guiffrida, 2018); and use of self‐regulated learning to improve multicultural awareness, skill development, and competence (Zeleke, Karayigˇit, & Myers‐Brooks, 2018).…”
Section: Teaching and Trainingmentioning
confidence: 99%